KOMUNIKASI NONVERBAL KEPALA MADRASAH DALAM MEMBERI KETELADANAN KEPADA GURU DI MAN 3 TABALONG - Chairul Echwan (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2023)
This research is motivated by the importance of nonverbal communication by madrasah principals in setting an example for teachers. In setting an example for madrasa head teachers, effective communication skills are needed, one of which is the ability to use nonverbal communication. The aim of this research is to determine the nonverbal communication of madrasah principals in providing examples to teachers and their obstacles. This type of research is field research using a qualitative descriptive approach. The research subjects were the Head of MAN 3 Tabalong and 3 teachers. Data collection techniques in this research used observation, interviews and documentation. Furthermore, data analysis is carried out by reducing the data first, followed by presenting the data until at the end there is drawing conclusions and verification. Based on the results of research regarding non-verbal communication of madrasa heads in giving examples to teachers at MAN 3 Tabalong, it shows that non-verbal communication through touch, such as showing thumbs up and happy hand movements, so that teachers are motivated and imitate what the madrasa head shows. Facial expressions, such as showing happiness, laughing and cheerfulness, so that the teacher is carried away in a good condition, then becomes a role model for the teacher. Eye contact shows focus and seriousness towards the teacher, thus making the teacher continue to be focused and serious about doing the things that have been carried out. Appearance, showing a neat appearance, according to the rules, and not excessive, so that the teacher is always neat, according to the rules, and not excessive in appearance. Touching, shaking hands and clapping, such as greetings, applause and praise, so that teachers become motivated by the appreciation made by the head of the madrasah. Proximity of distance, such as not too far and not too close, so that teachers feel comfortable and do not hesitate when interacting with the principal. Most teachers can emulate what the madrasah principal exemplifies. The obstacles faced by the madrasa head's nonverbal communication in providing examples to teachers at MAN 3 Tabalong, namely time, body condition, and the teacher's level of understanding.